Plant response to disturbance in a Mediterranean grassland: How many functional groups? - Lavorel, S; McIntyre, S; Grigulis, K (Journal of Vegetation Science, 2009)
. Data referring to changes in vegetation composition resulting from cattle exclosure and ploughing in a Portuguese pasture dominated by annuals were used to test hypotheses regarding the biology of species favoured or eliminated by disturbance in semi-natural herbaceous communities. These hypotheses were tested in two ways. First we compared the distribution of six a priori groups – grasses, small rosettes, large rosettes, small species with leafy stems, large species with leafy stems, legumes – across grazed, ploughed and undisturbed plots. In a second set of analyses we examined changes in the frequencies of individual biological attributes in response to grazing and ploughing. These analyses were carried out separately for grasses and dicot forbs. Overall, the species composition showed little response to either grazing or ploughing, though species dominance changed. This lack of responsiveness of species composition was attributed to the long history of intensive land use which has resulted in the loss of disturbance-intolerant species over entire landscapes. When considering a priori groups, small rosettes were indifferent to disturbance. grazing and ploughing showed that dominated. Large rosettes, large species with leafy stems and legumes were generally intolerant to both grazing and ploughing, though individual species may increase in response to disturbance. Small species with leafy stems were the only group favoured by grazing whereas ploughing favoured grasses. As to individual traits, grazing excluded large grass species with heavy seeds and promoted a flat rosette canopy structure and a small size, along with a moderate dormancy and protected inflorescences. In forbs, grazing favoured small species, as expected, while it excluded tall species, and, in contrast to earlier results, a rosette canopy. These attributes were consistent with responses of the a priori groups, though it would not have been possible to reconstruct groups directly from the attribute list. Ploughing had no effect on any of the forb traits. As to grass traits, flat- and short-statured species increased and heavy-seeded species decreased. Our analysis revealed two advantages of establishing plant functional classifications within life forms. Subgroups within forbs had contrasting types of behaviour. For the same trait patterns could differ within the grass group from within the forb group. Finally, this analysis emphasizes the need for plant functional classifications aiming at the identification of syndromes of co-occurring attributes rather than of lists of isolated traits of which actual combinations are not specified.
Keywords: Annual; disturbance; Grazing; Plant functional type; Ploughing; Portugal

Plant and soil nitrogen dynamics in mediterranean grasslands: a comparison of annual and perennial grasses - Joffre, R (Oecologia, 1990)
The predominance of annual species in the rangelands of southwestern Spain is not due only to climatic factors but is also strongly influenced by grazing management. Manipulating the grazing system in an experimental plot gave a vegetation structure with patches of annual grasses (mainly Vulpia ssp. and Bromus hordeaceus) and patches of perennial grasses (mainly Phalaris aquatica). This vegetation change allowed us to test the hypothesis that life-cycle differences between annual and perennial grasses affect soil nitrogen availability and plant uptake. Nitrogen availability, measured by in situ incubation, and nitrogen uptake were measured through the growing period (October to June). Amounts of in situ mineralized nitrogen over the whole growth phase were more important for soils supporting perennials (37 ppm) than for soils supporting annuals (27 ppm). The difference between the mineral nitrogen produced in situ and the mineral nitrogen accumulated during the same time in the soil allowed an estimation of the maximum mineral nitrogen quantity which can be taken up by the vegetation during each incubation period. The quantities accumulated over the year were 47 and 38 ppm (or 103 and 83 kg/ha) for soils supporting perennials and annuals respectively. For the same period, amounts of nitrogen immobilized in biomass production were 90 and 70 kg/ha for perennials and annuals respectively. During the autumn, a large proportion of mineral nitrogen was leached from soils supporting annual plants which had only just commenced germination. By contrast, the ability to use mineral nitrogen as soon as autumn rains occurred gave a competitive advantage to the perennial species, but only if they were protected from grazing during this period. The higher mineralization and use of this nitrogen reserve by perennials indicates that they made more efficient use of nitrogen resources than annuals, and validate the initial hypothesis.
Keywords: Annual; grassland; Nitrogen mineralization; nitrogen uptake; Perennial